Stimulation of methane oxidation potential and effects on vegetation growth by bottom ash addition in a landfill final evapotranspiration cover - Kim, Gil Won (Waste management (New York, N.Y.), 2016)
Copyright © 2016 Elsevier Ltd. All rights reserved.